Evaluation of factors influencing audience perception of Nollywood movies - Abdulhamid Badru; Hasrul Hashim; Adisa, R. M. (Penerbit Universiti Kebangsaan Malaysia, 2022)
The Nollywood phenomenon has remarkably become an international moviemaking culture, serving as one of the determinants of Nigerian perception formation on social and educational behaviours. Globalisation in the film industry impacts audience taste and perception, not only in the global free market but also among niche audiences. This audience segmentation occurred due to globalisation, enabling cross-border production or transnational cinema. This research investigates how the Nollywood audience in Nigeria perceives its movies and the factors that influence their perception. Audience perceptive elements in this research are classified as tripartite (education, entertainment, information). Using a semi-structured questionnaire, 387 were distributed, but only 367 were valid. The study employs a descriptive and regression analysis to showcase the frequency of audience perception and compare how effectively the factors affect audience perception. Based on the descriptive analysis, the results showed that Nollywood movies are mostly entertainment, followed by educative and informative. In addition, the regression results revealed that factors such as the level of income, occupation, tribe, the language of movies watched, triggers watching movies, genre, streaming platforms, time (weekdays, weekends, and times watching movies in a week) significantly influenced audience perception. Whereas time constraints (watching during weekdays and weekends) weakly influence audience perception. The findings suggest a need for Nollywood movies to pay more attention to audience expectations and experience in their dissemination to enhance audience perception of the movie industry.